PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA DAERAH (Studi Kasus Pemerintah Kota Palopo Tahun 2013-2019) - Musriani; Haliah (PT Wahana Global Education, 2025)
Research this has the purpose to determine and analyze the influence of income native region and fund balance of the shopping area of government Palopo City . The method in this study uses a survey method and data analysis by taking data in the form of a report on the realization of the APBD for 7 periods from 2013-2019 budget sourced from the Regional Financial and Asset Management Agency of Palopo City . Novelty of the research is an imitation of the research that already exist with several additions and updates to the data. The results of the analysis of the correlation indicates the relationship is very strong between revenues original area of the shopping area and the relationship is very strong fund balance to the shopping area . The test results of hypothesis is partially shows the influence of positive and significant between revenues original area of the shopping area and not there is influence significantly between the fund balance of the shopping area of the City of Palopo . The test results hypothesis is simultaneously or synchronously show that between revenues native region and fund balance of the Regional shopping Palopo City there is influence that significantly .